INTEGRATING ISLAMIC AND CIVIC EDUCATION: A PROJECT-BASED MODEL TO PREVENT CAROK VIOLENCE AMONG STUDENTS - Moh Fathur Rohman; Kholis Frendika (AL - IBRAH, 2026)
The persistence of carok (a cultural tradition of violent vengeance) among students in Bangkalan, Indonesia, poses a significant challenge to character education. This phenomenon is rooted in a distorted cultural interpretation of siri’ (honor), which legitimizes violence as a means of restoring dignity. This study aims to develop and evaluate the effectiveness of an integrative educational model combining Islamic Religious Education (PAI) and Civic Education (PKN) to prevent carok by fostering comprehensive Islamic conflict resolution skills. This study employed a qualitative case study design complemented by quantitative outcome measures to assess the effectiveness of the intervention. The research was conducted in three junior high schools in Bangkalan through in-depth semi-structured interviews with students, PAI and PKN teachers, and community leaders, participatory observation, and document analysis of lesson plans and student work. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing/verification. The findings indicate that students’ perceptions of self-esteem were strongly shaped by cultural constructs that legitimized violence. The implementation of a five-stage integrative project model conflict identification, values exploration (PAI), solution design (PKN), creative product development, and reflection facilitated a significant paradigm shift. Over the six-month intervention period, the model contributed to a 60% reduction in physical fights and a 45% increase in the use of peer mediation. The study demonstrates the effective synergy of Qur’anic values such as patience, anger management, and forgiveness with civic principles including human rights, legal awareness, and restorative justice, resulting in a more constructive understanding of conflict resolution among students. This integrative PAI-PKN project-based model offers an effective educational strategy for deconstructing violence-oriented understandings of honor and promoting peaceful conflict resolution. The findings underscore the importance of sustainable teacher training, curricular alignment, and strong collaboration among schools, families, and communities.